Peningkatan Literasi Artificial Intelligence Guru SMA Negeri 2 Negara Melalui Workshop dan Pendampingan Berbasis Praktik - I Putu Agus Swastika (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The digital competence gap among educators in adopting Artificial Intelligence (AI) poses a major challenge to implementing the Merdeka Curriculum, which demands adaptive and personalized learning. This community service activity aimed to enhance AI literacy among teachers of SMA Negeri 2 Negara, Jembrana Regency, through an introduction to basic AI concepts, ethics of AI use in education, and practical training on generative and adaptive AI tools (MagicSchool.ai and NotebookLM). The implementation method consisted of needs analysis, pre-test, hands-on workshop, one-month implementation mentoring, and evaluation through post-test and satisfaction survey. The activity was conducted on January 30, 2026 and was attended by 75 teachers. The results showed very high participant enthusiasm, with all participants stating that the workshop was beneficial. The average post-test score reached 89.47%, reflecting excellent understanding of the material. The highest-scoring items (97.40%) were basic AI concepts and the working principle of Large Language Models, while one item on the symbolic AI period needed reinforcement (73.70%). The teachers were able to understand academic integrity in the AI era and began exploring the creation of AI-assisted interactive teaching materials. In conclusion, this workshop successfully transformed teachers' initial perceptions and competencies in utilizing AI ethically and adaptively, thus contributing to the improvement of learning quality in schools.